‘Everyone Should Be Like the People’: Elite and Popular Religion and the Counter Reformation - Johnson, Trevor (Studies in church history, 2006)
It is now over two decades since a cluster of studies by Natalie Zemon Davis, Bob Scribner, Marc Venard, Roger Chartier, Richard Trexler, William Christian, Carlo Ginzburg and others significantly modified our ways of thinking about religion in early modern Europe and in particular about the relationship between ‘elite’ and ‘popular’ religion, or as many had conceived it, between religion as preached and religion as practised. It had been simpler when writers who thought about such things had drawn neat boundaries between elite and popular and regarded communication between them as an exclusively one-way, top-down, process. They had also tended to regard the popular aspect of the polarity as qualitatively inferior to its elite corollary, depicting it variously as instrumental, functional, un-spiritual, somatic, irrational, unreflective, mechanical, amoral, magical or superstitious, or indeed as all of these things together, as if ‘the people’, a group generally defined in class terms as the socially subordinate, exhibited a vast collective unconscious. Additionally, much ethnography had taken such a divide as axiomatic, the German Volkskunde tradition, for example, often positing a process of transmission or ‘sinking’ of cultural forms from the elite down to the popular level. Such assumptions, which moreover uncritically reflected a notion of ‘religion’ which is restricted to a formal doctrinal corpus, defined and authenticated by the very body charged with its maintenance, were damaged by the historical revolution of the 1970s and 1980s and will not do for most scholars now, despite having informed a number of still influential historical schemata.